Adoption of gender-responsive budgeting (GRB) by an Italian municipality - Giovanna Galizzi; Gaia Viviana Bassani; Cristiana Cattaneo (Administrative Sciences, 2018)
Over the past few decades, many governments throughout the world have promoted gender-responsive budgeting (GRB). With its focus on equality, accountability, transparency and participation in the policy-making process, GRB shares some relevant principles with public governance that call governments at national and subnational levels to rethink their roles in the whole economic system. This worldwide political and managerial interest does not find sufficient space in academic discussion, mainly in terms of public administration and management studies. Adopting an interpretative approach, the present study aims to investigate how an Italian municipality has involved stakeholders in the GRB process. The case study shows that, when GRB is fully developed, the stakeholders involved are both internal and external, and these multiple actors, in pursuing gender equality, cooperate to achieve a common, public aim. In this way, GRB gives effectiveness to the public decision-making process, contributing to greater incisiveness in the local government's management and creation of a gender-sensitive governance process.
Keywords: 350; gender-responsive budget; public governance; gender equality; stakeholder engagement